Pattern transfer of microstructures between deeply etched surface for MEMS applications. (December 2016) - Joyce, Robin; Yadav, Supriya; Sharma, Akash Kumar; Panwar, Deepak Kumar; Bhatia, Ravi Raj; Varghese, Soney; Akhtar, Jamil
Abstract: Photolithography plays a vital role in micromachining process however; coating a thin and uniform resist layer on a non-planar surface is a challenging task for micro-electro-mechanical system (MEMS). Conventional spin coating of photoresist (PR) over an un-even surface would deliver streaks all over the wafer surface. Spray coating of PR is a promising technique when compared to other candidates. This paper presents an efficient pattern transfer of microstructures between the bulk micromachined cavities over silicon and glass wafers using an uncommon photoresist mixture being spray coated. The method is simple and highly cost effective. Finally we implemented this technique for a MEMS application to prove the feasibility of spray coating for microstructure fabrication.